Reverse Domain Hijacking - W., Fahed (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2019)
PrologueThere is often a conflict between domain names owners and trademarks holders’ rights, and If a party has a specific domain name but the other party owns trademark rights with that name, it's likely that there's a problem, one of these problems presented by domain names hijacking. From a legal perspective, domain names hijacking taking important place in cyberspace challenges, in this scenario, domain names rights are infringed when a third party managed to transfer a domain name to his account without illegal right to be able to resell it and gain moneyAssumptionThe point of this research arises from that UDPR policy is not enough to solve the reverse domain hijacking phenomena, and then comprehensive legislation is needed to solve this phenomenon.MethodologyThe methodology will depend on inductive approach based on Selected and analyses court decisions with legal texts. This paper will try to provides scholarly appraisal of the legal and policy related to domain names hijacking.